Media And Woman In Parliament (Analysis Contents News Kompas.Com According to Standpoint theory) - Pellu, Mira Natalia (Jurnal Ilmu Sosial Mamangan, 2025)
The media not only gives a large portion of news coverage to men but also helps justify the bias about women that has been developing in society. This article is specifically to find out the description of the news coverage of female members of the Indonesian House of Representatives in the Kompas newspaper. com. Method analysis Contents used to news in period May 2019-April 2021 with objectivity standpoint theory as preference conceptually. Results study shows that in Indonesia women are starting to gain trust to be in the public space, but parliament is still designed for men. This can be seen from the fact that men are still trusted to lead meetings, make decisions and so on.